IMPLEMENTASI KONSEP KEWARGANEGARAAN DALAM PENDIDIKAN DI INDONESIA - Hasibuan, Novita Sary; Naysya Desky; Serlin Fitriana; Sapta Kusuma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Political science is an important foundation for understanding the concept of citizenship, which forms the basis of citizenship education in Indonesia. This journal discusses the basic concepts of political science and its relevance to education, particularly in shaping good character in citizens through the learning process. This study uses a literature review method to analyze the relationship between political science theories and the practice of citizenship education in schools. The results of the study show that an understanding of the state, the rights and obligations of citizens, and democratic values is very important to instill in students as future responsible citizens. Educators have a strategic role in transforming the concepts of political science into meaningful and contextual learning.